Molecular modeling study of pristine and thermally modified ZIF-8: applications on carbon capture - Finamor, Matheus (2023)
In this work, we study Metal-Organic Frameworks (MOFs) as a new material able to capture CO2 efficiently. These frameworks are promising regarding carbon capture due to high surface areas, tunable pore size, and a high potential for industrial-scale production. In particular, we study a specific MOF, the Zeolitic Imidazolate Framework 8 (ZIF-8), composed of zinc coordinated with imidazole, structured in a sodalite framework. Through first- principles calculations based on the Density Functional Theory (DFT) using a functional with nonlocal van der Waals correction, the optB86b, we investigate CO2 adsorption in ZIF-8 by identifying different adsorption sites and their respective adsorption energy. Furthermore, using atomistic simulations based on Grand Canonical Monte Carlo, the selectivity of carbon considering reservoirs with different mixtures at distinct concentrations and thermodynamic conditions was calculated. Moreover, recent experimental findings indicate that thermal post- treatment of ZIF-8 can enhance its carbon capture capability. Therefore, we modeled propositions of possible defects induced by this kind of treatment and study their stability and how they affect adsorption. Our results indicate that thermal treatments near 900 ºC can enhance carbon capture up to 15 to 18.5 times the CO2 uptake of pristine ZIF-8. Since thermal treatments are cheap and easy to be scaled, these treatments can designate ZIF-8 treated as a proper filler to be used in mixed-matrix membranes, enabling a membrane design that can be efficient and economically viable to capture carbon.